A DESCRIPTIVE STUDY TO ASSESS THE KNOWLEDGE AND ATTITUDE OF URBAN AND RURAL POPULATION REGARDING TUBERCULOSIS AND ITS MANAGEMENT - PERIADURACHI KUMAR; DR. K.R.JOHN (International Journal of Pharma and Bio Sciences, 2016)
Tuberculosis continues to be a burden for India with the country still registering a high death rate for and it is completely curable by early diagnosis and treatment regime. Lack of knowledge about the disease and treatment is the major cause for this. The study was aimed to assess the knowledge and attitude of urban and rural general population regarding tuberculosis and its managements in selected villages at Bangalore. Descriptive research design was adopted and systematic sampling technique was used to select the sample. The study was conducted in two villages of Bangalore, where 235 samples from urban village and 235 samples from rural village who satisfied the sampling criteria and voluntarily consented for the study were selected. Structured questionnaire for assessing the knowledge and 5 point scale for assessing the attitude were used to collect data from the samples. The data obtained was analyzed using descriptive and inferential statistical methods and interpreted in relation to the objectives of the study. The level of significance was set at p<0.05. In urban population, knowledge of tuberculosis and its management was adequate in 4.68% of the participants where as in rural population it was adequate in only 0.85% of the participants. In urban population the attitude was found to be good for 91.91% and in rural population it was 97.4%. Study concludes that the general population should be sensitized with the knowledge of tuberculosis and its management to enhance their understanding and to have a better attitude